On k-ideals of semirings - M. K. Sen; M. R. Adhikari (International Journal of Mathematics and Mathematical Sciences)
Certain types of ring congruences on an additive inverse semiring are characterized with the help of full k-ideals. It is also shown that the set of all full k-ideals of an additively inverse semiring in which addition is commutative forms a complete lattice which is also modular.